2004
DOI: 10.1007/s11182-005-0049-6
|View full text |Cite
|
Sign up to set email alerts
|

Complexing and photoprocesses in a PRODAN molecule

Abstract: 535.37The effect of hydrogen bond on the spectral-luminescent properties of the PRODAN molecule -water complexes is studied. Quantum chemical calculations are performed for the ground and fluorescent equilibrium states of a free PRODAN molecule and its complexes with Н 3 О + . It is shown that significant changes occur in the geometry of the molecule in the fluorescent state. To describe the fluorescent state, account was taken of the changes in the electron density (population) on the bonds and atoms in trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The observation of two emission bands is consistent with the presence of two distinct bands reported in several theoretical and experimental investigations of PRODAN absorption transitions. 18,19,21,67,68 Definitive assignments of these bands have not been reported, but the variation in emission wavelength from both states with solvent polarity indicates that both have substantial charge transfer character. It is noteworthy that the redder spectrum decays at the slower rate and is more intense than the blue component in toluene and acetonitrile.…”
Section: Resultsmentioning
confidence: 98%
“…The observation of two emission bands is consistent with the presence of two distinct bands reported in several theoretical and experimental investigations of PRODAN absorption transitions. 18,19,21,67,68 Definitive assignments of these bands have not been reported, but the variation in emission wavelength from both states with solvent polarity indicates that both have substantial charge transfer character. It is noteworthy that the redder spectrum decays at the slower rate and is more intense than the blue component in toluene and acetonitrile.…”
Section: Resultsmentioning
confidence: 98%
“…PRODAN and LAURDAN are known to be used in several membrane studies. Their photophysical properties have been extensively studied and the existence of several states has been established, of PRODAN and its analogs, in both the ground and excited states [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. It was shown that the fluorescence characteristics of PRODAN in 1,4-dioxane are due to two forms of the dye in the ground and two forms of PRODAN in the excited state, which differ in the magnitude of the dipole moment and the conformation of the carbonyl group [19].…”
Section: Introductionmentioning
confidence: 99%